2014
DOI: 10.1007/s13365-014-0285-z
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviruses, an expanding threat in public health: focus on dengue, West Nile, and Japanese encephalitis virus

Abstract: The flaviviruses Dengue, West Nile, and Japanese encephalitis represent three major mosquito-borne viruses worldwide. These pathogens impact the lives of millions of individuals and potentially could affect non-endemic areas already colonized by mosquito vectors. Unintentional transport of infected vectors (Aedes and Culex sp), traveling within endemic areas, rapid adaptation of the insects into new geographic locations, climate change, and lack of medical surveillance have greatly contributed to the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 227 publications
0
100
0
2
Order By: Relevance
“…Japanese Encephalitis Virus (JEV) is a member of the Flaviviridae family. Other mosquito-borne, and medically important pathogens viruses belonging to this family are DENV and West Nile virus [59]. JEV is a neurotropic virus which causes encephalitis in humans and has a mortality rate ranging from 25% to 30% [59].…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
“…Japanese Encephalitis Virus (JEV) is a member of the Flaviviridae family. Other mosquito-borne, and medically important pathogens viruses belonging to this family are DENV and West Nile virus [59]. JEV is a neurotropic virus which causes encephalitis in humans and has a mortality rate ranging from 25% to 30% [59].…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
“…This genus also includes dengue virus (DENV) 1–4, West Nile virus (WNV) 1 and 2, Yellow Fever virus (YFV), and Japanese encephalitis virus (JEV) I–V (Lindenbach and Rice, 2003). The flaviviruses infect a wide range of hosts such as rodents, pigs, birds, non-human primates, and humans (Daep et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…6 In contrast to DENV, outbreaks of WNV are often self-limiting, with humans acting as dead-end hosts for the virus, where the potential for epidemics is directly influenced by a combination of the density of mosquito vectors and the presence of avian reservoirs. 7 Previous studies have identified the presence of DENV antibodies in native Haitians; however, most recent studies have focused on active infections and/or seroconversion in nongovernment organization workers or missionaries to Haiti; thus, the disease burden of DENV in the native population remains to be adequately characterized. [8][9][10] Furthermore, even though cases of WNV have been reported in Haiti and WNV has been detected in birds and mosquitos from the Dominican Republic, no active surveillance for WNV has taken place for over a decade.…”
Section: Introductionmentioning
confidence: 99%